PCR DETECTION OF COXIELLA BURNETII FROM BULL SEMEN SAMPLES USED FOR ARTIFICIAL INSEMINATION - Yatsentyuk S.P. (Russian Journal of Agricultural and Socio-Economic Sciences, 2019)
444 samples of bull frozen semen used for artificial insemination from local and foreign breeding centers were investigated by PCR for the presence of DNA of Coxiella burnetii. C. burnetii DNA was detected in 32 semen samples from US and was not found in semen straws from local breeding centers and breeding centers of Netherlands and Great Britain. According to the results, it is evident that despite the restrictions and controls on the international movement of semen, bull semen is still a potential source of pathogen transmission.